Resource Use Efficiency in Pineapple Cultivation – a Case Study from Manipur, India - Thingbaijam, Laxmi; Das, K. K.; Singh, N. R.; Zimisai, S. (International Journal of Bio-resource and Stress Management, 2015)
The study analysed the resource use efficiency of pineapple (Ananus comosus) by using Cobb-Douglas production function with a unique set of 100 randomly selected sample farmers of Manipur district during 2009-10. The pineapple can be a good economic activity of Manipur. Farmers could earn net income of ` 1,73,312.20 ( 2888.54) ha-1. With a satisfactory benefit-cost ratio of 4.05. The average cost of cultivation was ` 57303.02 ( 955.05) ha-1. Small farmers (category-I) were found to have more profit compared to big farmers (Category-II). This could be justified with the higher values of their resource use efficiency in respect of planting material (sucker), plant protection chemical, manure and fertilizers etc. Production function analysis identified expenditure on sucker, manures and fertilizers, plant protection chemicals, labour wage being the major cost components. Marginal value product (MVP) analysis also collaborated these findings. Judicious use of sucker, plant protection chemicals and manures and fertilizers had been found to have good and positive impact on production and the net return. Use of excess human labour made the farming less remunerative which advocated engagement of labour at optimal level.